Identification of an Infected Urachal Cyst Using Point-of-Care Ultrasound. Issue 6 (June 2021) - Austin, Samuel; Jersey, Candice; Soltis, Michael; Chicaiza, Henry
Abstract : Abstract: This case describes a 6-year-old girl who presented to the pediatric emergency department with 3 days of fever and suprapubic pain in the setting of 1 month of worsening, dull abdominal pain. On presentation, she had a tender, erythematous, and fluctuant mass on her lower abdomen. Point-of-care ultrasound was used to identify an abnormal fluid collection anterior to her bladder, suspicious for an infected urachal cyst. In this case, point-of-care ultrasound helped identify this uncommon finding in a timely fashion, which expedited definitive care and prevented unnecessary exposure to ionizing radiation.